Comparative analysis of gut microbiota and immune genes linked with the immune system of wild and captive Spodoptera frugiperda (Lepidoptera: Noctuidae). (January 2023) - Zheng, Renwen; Cheng, Luoling; Peng, Jun; Li, Qianqian; Yang, Fan; Yang, Dehua; Xia, Yuxian; Tang, Qingfeng
Abstract: The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), is one of the most highly polyphagous invasive pests causing serious damage to maize crops in China. However, little is known about the gut immune responses to the environment, particularly along the migration routes in Jianghuai, China, throughout the autumn and winter. In this study, high-throughput sequencing and real-time quantitative PCR (RT-qPCR) were employed to examine the variations in immune genes and gut microbiome communities between captive and wild fall armyworm populations. Results showed that the diversity and community of the gut's microbes were higher in wild populations, and the average weighted UniFrac distance between bacterial taxa varied. A wide variety of immune genes were more abundant in the wild populations than in others. Results indicated that diets and different survival conditions impacted the gut microbiota and immune system of S. frugiperda, which was crucial for environmental adaptation. These differences in gut microbiota and immune responses between wild and captive Fall armyworms are critical for comprehending the symbiotic relationship between microbes, immune genes, and hosts. They also highlight the need for increased focus on developing more effective and environmentally friendly pest control methods. Highlights: Gut microbiota analysis of the polyphagous insect pest Spodoptera frugiperda was accomplished. A large amount of Immune genes could be significantly induced in response to field environment. The results might be helpful to comprehend immune function of Fall Armyworms for field adaption.